The impact of personality and coping on the development of depressive symptoms in adult burns survivors - Andrews, R.; Browne, Allyson; Drummond, P.; Wood, F. (Pergamon Press, 2010)
This prospective study examined the extent to which the personality traits neuroticism, extraversion and agreeableness and coping styles approach, avoidant and ambivalent contribute to the development of depressive symptoms in adult burns survivors at three months post-injury. Participants were 70 adult burns survivors admitted to Royal Perth Hospital in Western Australia between June 2007 and February 2008. Personality was assessed using the NEO Personality Inventory-Revised (NEO-PI-R), coping was evaluated with the Coping with Burns Questionnaire (CBQ) and depressive symptoms were measured using The Centre for Epidemiologic Studies Depression Scale (CES-D). Twenty one percent of retained participants at three months (n = 29) reported clinically significant depressive symptoms. There were no significant relationships between depressive symptoms at three months and demographic or burn characteristics. Neuroticism significantly predicted depressive symptoms at three-month follow-up and this relationship was significantly mediated by avoidant coping. In addition, extraversion, avoidant coping and approach coping were all significant and independent predictors of depressive symptoms at three months. These findings suggest that burns patients at greatest risk of developing clinically significant depressive symptoms may be identifiable in the acute recovery phase. © 2009 Elsevier Ltd and ISBI.